Effect of weld zone and corner with cold bending effect on wrinkling of rectangular welded tube in rotary draw bending. (December 2020) - Liu, Hailong; Liu, Yuli; Zhang, Peng; Du, Xiaoyu
Abstract: Wrinkling of QSTE700 high strength steel thin-walled rectangular welded tube is easy to occur in rotary draw bending (RDB) process due to the existence of non-homogeneous weld zone and corner with cold bending effect. So the FE model of RDB of QSTE700 rectangular welded tube considering weld zone and corner with cold bending effect was established. Based on this FE model, the effect of weld zone and corner with cold bending effect on wrinkling of inner flange and side wall of rectangular welded tube in RDB was researched. The results showed that: when weld zone and corner with cold bending effect were studied separately, weld zone both increased the wrinkling height of inner flange and side wall. However, the influence of corner with cold bending effect on wrinkling height of side wall and inner flange was inconsistent, it reduced the wrinkling height of inner flange, but increased the wrinkling height of side wall. When the weld zone and corner interacted, the coupling effect between weld zone and corner with cold bending effect on wrinkling resulted in the decrease of wrinkling height of inner flange and increase of wrinkling height of side wall of rectangular welded tube in RDB. Highlights: The wrinkling characteristics of rectangular welded tube were revealed in rotary draw bending process (RDB). The separate effect of weld zone and corner on wrinkling of rectangular welded tube was researched in RDB. The coupling effect between weld zone and corner on wrinkling of rectangular welded tube was studied in RDB.